Indeks Kualitas Pelayanan Pernikahan oleh KUA di Kabupaten Kebumen Jawa Tengah - Zakiyah Zakiyah (Balai Penelitian dan Pengembangan Agama Makassar, 2017)
This article concerns on the quality index of marriage service provided by office of ministry of religious affairs (KUA) in Kebumen district, Central Java province. This is an important topic to be discussed since this is one of the public services offered by the government especially Ministry of Religious Affairs Republic Indonesia. This paper was written based on a research using a quantitative approach which is conducted at KUA Kebumen sub-district and KUA Pejagoan sub-district. Data was collected using questioners that were given to the respondents in two sub-districts. Then, data was analyzed using ServQual (Service Quality) theory. This theory looks at the gap between the expectation and the perceived services gained by the consumers. Results of this study show that generally the quality of such service is in a good and a very good category, however there is a negative gap, so that it needs some correction to betterment.